Benzyl Isothiocyanate and Resveratrol Synergistically Alleviate Dextran Sulfate Sodium-Induced Colitis in Mice - Jianan Liu; Qian Zhang; Hongshun Hao; Jingran Bi; Hongman Hou; Gongliang Zhang (Foods, 2024)
The aim of our study was to investigate whether the combination of benzyl isothiocyanate (BITC) and resveratrol (RES) has a synergistic effect on the inhibition of inflammation in colitis. The results revealed that the BITC and RES combination (BITC_RES) was more effective than either substance alone at significantly alleviating the symptoms of dextran sodium sulfate (DSS)-induced colitis in mice, including the prevention of colon shortening and loss of body weight, a reduction in the disease activity index, and prevention of colon damage. Similarly, compared with the DSS group, BITC_RES reduced myeloperoxidase (MPO) and inducible nitric oxide synthase (iNOS) levels in the mouse colon by 1.4–3.0-fold and 1.4-fold, respectively. In addition, the combination of BITC and RES upregulated the inflammatory factor IL-10 by 1.3- and 107.4-fold, respectively, compared to the individual BITC and RES groups, whereas the proinflammatory factors, including TNF-α, IL-1β, and IL-6, were downregulated by 1.1–7.4-, 0.7–3.6-, and 0.6–2.6-fold, respectively, in the BITC_RES group compared with the individual groups. Gut microbiome analysis indicated that BITC_RES remodeled the structure of gut bacteria at the phylum, family, and genus levels, upregulating the abundance of the phylum Bacteroidetes and the family Muribaculaceae and the genus norank_f_Muribaculaceae and downregulating the abundance of the phylum Firmicutes. Significant correlations between the relative levels of these proinflammatory cytokines and changes in the gut microbiota were found using Pearson’s correlation analysis. BITC and RES exhibited synergistic effects by reshaping the gut microbiota and modulating the level of serum cellular inflammatory factors, thus exerting a protective effect against colitis.